Berkah Atau Bencana? Desentralisasi Sumber Daya Alam Dan Nasib Kesejahteraan Masyarakat: Sebuah Kajian Literatur - Savitri, Evi; Tjenreng, Muhammad Baharuddin Zubakhrum (Pascasarjana STIE Amkop Makassar, 2025)
Decentralization of natural resources in Indonesia aims to improve people's welfare through regional autonomy in natural resource management. However, this policy faces challenges such as unequal distribution of benefits, overexploitation, and potential corruption. This study aims to analyze the impact of natural resource decentralization on community welfare using a Systematic Literature Review (SLR) approach. Data were collected from reputable journals using bibliometric techniques with VOSviewer and Publons/Perish software to map research trends. The results show that decentralization can improve people's welfare if it is supported by good governance, community participation, and strict regulations. Conversely, under conditions of weak governance, decentralization exacerbates social inequality and damages the environment. Comparative studies with other countries, such as Brazil and India, show that the success of decentralization depends on oversight mechanisms and the involvement of local communities. The conclusions of this study emphasize the importance of transparency, equitable distribution of benefits, and strengthening the capacity of local governments to manage natural resources sustainably. Policy recommendations include increased accountability, a natural resource endowment mechanism, and stricter oversight of resource exploitation.